Strain and Thermally Induced Magnetic Dynamics and Spin Current in Magnetic Insulators Subject to Transient Optical Grating - Wang, Xi-Guang; Chotorlishvili, Levan; Berakdar, Jamal (Frontiers in Materials, 2017)
We analyze the magnetic dynamics and particularlythe spin current in an open-circuit ferromagnetic insulator irradiated by two intense, phase-locked laser pulses. The interference of the laser beams generates a transient optical grating and a transient spatio-temporal temperature distribution. Both effects lead to elastic and heat waves at the surface and into the bulk of the sample. The strain induced spin current as well as the thermally induced magnonic spin current are evaluated numerically on the basis of micromagnetic simulations using solutions of the heat equation. We observe that the thermo-elastically induced magnonic spin current propagates on a distance larger than the characteristic size of thermal profile, an effect useful for applications in remote detection of spin caloritronics phenomena. Our findings point out that exploiting strain adds a new twist to heat-assisted magnetic switching and spin-current generation for spintronic applications.